Catalog of the genus Schmidtiana Podaný 1971 (Coleoptera: Cerambycinae) in the Philippines with notes on species variation and key to the species - Medina, Milton Norman; Camposo, Pheobe; Ytang, Jeanlie; Seniel, John Glen; Buenavente, Perry; Vives, Eduard (Zootaxa, 2025)
This paper presents a catalog of Philippine species of the genus Schmidtiana Podaný, 1971, with updated distributional records from the Eastern Mindanao Biodiversity Corridor. It also provides information on species-level variation, high-definition images of type materials and reference collections, and an identification key to the Philippine species of Schmidtiana. A neotype of S. palawana (Schultze, 1922) is also designated and deposited in the Philippine National Museum.